Minimally Invasive Mini-orbitozygomatic Approach for Clipping an Anterior Communicating Artery Aneurysm: Virtual Reality Surgical Planning - González Romo, Nicolás; Ravera Zunino, Franco (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Virtual reality (VR) has increasingly been implemented in neurosurgical practice. A patient with an unruptured anterior communicating artery (AcoA) aneurysm was referred to our institution. Imaging data from computed tomography angiography (CTA) was used to create a patient specific 3D model of vascular and skull base anatomy, and then processed to a VR compatible environment. Minimally invasive approaches (mini-pterional, supraorbital and mini-orbitozygomatic) were simulated and assessed for adequate vascular exposure in VR. Using an eyebrow approach, a mini-orbitozygomatic approach was performed, with clip exclusion of the aneurysm from the circulation. The step-by-step process of VR planning is outlined, and the advantages and disadvantages for the neurosurgeon of this technology are reviewed.
Keywords: virtual reality; intracranial aneurysm; microsurgery; skull base